Ivocard Development As a Media For Learning English Vocabulary for Children Aged 4-5 Years - Viora Budiman, Jovinska; Kurniawan, Mozes (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2022)
Purpose – English is an investment in the future that can increase self-potential; therefore, early childhood needs to know English. The introduction of English in early childhood can use learning media. This study aims to develop iVocard media as a medium for learning English vocabulary in early childhood 4-5 years.Design/methods/approach – This study uses Research and Development, with the subjects of this research being TK A students at BPK PENABUR Cimahi. Data was collected using observation, documentation, and questionnaire methods using a Likert scale of 1-5, then analyzed using descriptive analysis.Findings – The results showed that the iVocard media was in the “very appropriate” category in the material and media validation test. In both validation tests, there are a few suggestions for improvements to the iVocard learning media. Thus, the iVocard learning media can be used in the next stage, the trial stage.Research implications/limitations – The feasibility of iVocard learning media as a means to learn and improve English vocabulary for children aged 4-5 years.Practical implications – This research implies that English vocabulary learning media in early childhood can use card media, such as iVocard, to make learning more exciting and fun for children.Originality/value – This study uses learning media from iVocard, which can be used for learning in early childhood, especially for children aged 4-5 years.Paper type: Research paper